(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
The work focused on the evaluation and optimization of production quality of recycled paper for toilet tissue production in Anex manufacturing industry. Literature review revealed that no study has ever been carried out specifically and existing literatures have not intensively expressed its prediction and optimization of their production quality. The case company has no specific method of foreseeing and improving in the future the quality of the production output. This serves as the knowledge gap which the researcher tends to reveal. Data on the production yield were collected from the industry covering a period of six months. The graphical models developed using MatLab and Linear regression techniques in plotting the production input (raw material) against defective product produced measures of accuracy of the models. The MatLab technique produced a model with a measure of accuracy (MSE) of 290.06 while Linear regression technique produce a measure of accuracy (MSE) of 268.86. From the results of the models, it can be deduced that the model with lesser error is the more appropriate method to achieve the best product quality. The models were validated using response surface plots, which give the same measures of accuracies. Keywords: Recyclable paper, Production yield, Graphical models, Measures of accuracy.